Spaces of longing and belonging : territoriality, ideology and creative identity in literature and film - Le Juez, Brigitte, 1959-; Richardson, Bill, 1953- (Spatial practices, 2019)
Spaces of Longing and Belonging offers the reader theoretical and interpretative studies of spatiality centered on a variety of literary and cultural contexts. It brings new and complementary insights to bear on creative uses of spatiality in artistic texts and generally into the field of spatiality as a cultural phenomenon, especially, although not exclusively, in terms of literary space. Ranging over questions of aesthetics, politics, sociohistorical concerns, issues of postcoloniality, transculturality, ecology and features of interpersonal spaces, among others, the essays provide a considerable collection of innovative pieces of scholarship on important questions relating to literary spatiality generally, as well as detailed analyses of particular works and authors. The volume includes ground-breaking theoretical investigations of crucial dimensions of spatiality in a context of increased global awareness.